Beyond Amyloid and Tau: The Critical Role of Microglia in Alzheimer’s Disease Therapeutics - Daniela Dias; Renato Socodato (Biomedicines)
Alzheimer’s disease (AD) is traditionally viewed through the lens of the amyloid cascade hypothesis, implicating amyloid-beta and tau protein aggregates as the main pathological culprits. However, burgeoning research points to the brain’s resident immune cells, microglia, as critical players in AD pathogenesis, progression, and potential therapeutic interventions. This review examines the dynamic roles of microglia within the intricate framework of AD. We detail the involvement of these immune cells in neuroinflammation, explaining how their activation and response fluctuations may influence the disease trajectory. We further elucidate the complex relationship between microglia and amyloid-beta pathology. This study highlights the dual nature of these cells, which contribute to both aggregation and clearance of the amyloid-beta protein. Moreover, an in-depth analysis of the interplay between microglia and tau unveils the significant, yet often overlooked, impact of this interaction on neurodegeneration in AD. Shifting from the conventional therapeutic approaches, we assess the current AD treatments primarily targeting amyloid and tau and introduce novel strategies that involve manipulating microglial functions. These innovative methods herald a potential paradigm shift in the management of AD. Finally, we explore the burgeoning field of precision diagnosis and the pursuit of robust AD biomarkers. We underline how a more profound comprehension of microglial biology could enrich these essential areas, potentially paving the way for more accurate diagnostic tools and tailored treatment strategies. In conclusion, this review expands on the conventional perspective of AD pathology and treatment, drawing attention to the multifaceted roles of microglia. As we continue to enhance our understanding of these cells, microglial-focused therapeutic interventions emerge as a promising frontier to bolster our arsenal to fight against AD.